2000
DOI: 10.1038/sj.bmt.1702080
|View full text |Cite
|
Sign up to set email alerts
|

Role of high-dose therapy and initial response in survival of poor-risk patients with aggressive non-Hodgkin's lymphoma: a retrospective series on 126 patients from a single center

Abstract: Summary:It is now established that a subgroup of non-Hodgkin's lymphoma (NHL) patients probably benefit from highdose therapy (HDT). We therefore retrospectively analyzed survival of 126 consecutive patients with large cell lymphoma (LCL) and high-intermediate (HI) or highrisk (H) age-adjusted international prognostic index (Aa-IPI). They received either standard chemotherapy (CT) (66 patients), or HDT (60 patients). Distribution of the Aa-IPI scores showed no statistical significant difference between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This intrathecal regimen represents the standard treatment used at our institution for both involved and non‐involved cerebrospinal fluid. 24, 25, 30…”
Section: Methodsmentioning
confidence: 99%
“…This intrathecal regimen represents the standard treatment used at our institution for both involved and non‐involved cerebrospinal fluid. 24, 25, 30…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12] Durable responses and a high rate of cure have also been observed after ASCT in patients with poor prognosis recurrent or refractory mediastinal large cell lymphoma. [12][13][14] In the setting of large cell lymphomas the GELA (Groupe d'Etude des Lymphomes de l'Adulte) study clearly demonstrated that patients with high, high-intermediate risk disease according to AA-IPI had a poor out-come when treated with conventional chemotherapy, but had survivals significantly improved by high-dose therapy and ASCT. [15][16][17] The aim of our study was to evaluate the role of an early intensification treatment integrating induction CHT, ASCT and RT in patients with primary MLCL with sclerosis presenting with adverse prognostic factors.…”
mentioning
confidence: 99%
“…There is a consensus that high-clinical-risk DLBCL subjects require a risk-adapted therapy, because intensification of chemotherapy with autologous stem-cell transplantation (ASCT) has been shown to improve the prognosis for these high-risk patients in previous randomised clinical trials [1][2][3][4]. Nevertheless, the therapeutic protocols used for these patients have a high morbidity, associated with ASCT and the use of multiple drugs.…”
Section: Introductionmentioning
confidence: 99%